Sensitivity of influenza virus to ultraviolet irradiation - Hessling, Martin; Gierke, Anna-Maria; Sicks, Ben; Fehler, Nicole; Vatter, Petra (German Medical Science GMS Publishing House, 2022)
Background: The measures implemented against the coronavirus pandemic also led to a sharp decline in influenza infections in the 2020/2021 flu season. In the meantime, however, the number of influenza infections has risen again; it is known from history that influenza viruses can also trigger severe pandemics. Therefore, we investigated the efficacy of ultraviolet radiation in the spectral range of 200-40 for inactivating influenza viruses.Materials and methods: The scientific literature was searched for published ultraviolet (UV) irradiation experiments with influenza viruses and the results were standardized by determining the lg-reduction dose. The results were then sorted and analyzed by virus type and wavelength as far as possible.Results: The scope of the published data sets was limited and revealed large variations with regard to the lg-reduction dose. Only for experiments with influenza viruses in liquid media in the UVC spectral range around 260 nm - the emission range of commonly-used mercury vapor lamps - was there sufficient data to compare virus types. No significant difference between the virus (sub-) types was observed. The lg-reduction dose in this spectral range is 1.75 mJ/cm (median). It was also shown that influenza viruses are particularly sensitive in the far-UVC spectral range (200-230 nm). Conclusion: UVC, including far-UVC, is suited for influenza virus inactivation as long as the viruses are in UVC-transparent materials. A large difference in the UV sensitivity of different influenza viruses from the last approx. 100 years could not be detected. Thus, it is reasonable to assume that future influenza viruses will also be similarly UV-sensitive or that UV can also inactivate new influenza viruses.